Two-degree-of-freedom MIMO control for hydraulic servo-systems with switching properties. (February 2020) - Schröders, Simon; Maier, Clemens C.; Ebner, Wolfgang; Fidlin, Alexander; Hametner, Christoph
Abstract: Today's automotive industry is faced with the challenge of increasing the energy efficiency of passenger cars to meet ever tightening emissions regulations. An approach to overcome these challenges is the electrification of auxiliary units of the vehicle, such as the pump drive of a hydraulic servo-system for clutch actuation in automatic transmissions (AT) or dedicated hybrid transmissions (DHT). In this context, the model-based derivation of a nonlinear feedforward control law by application of input–output linearization to a non-flat system, is presented. The underlying model, which shows switching behaviour, is derived by simplification of a physical model of the investigated hydraulic servo-system with switching properties. The control objective consists in providing the required system pressure and volume flow for fast and accurate clutch actuation through operation of several servo-valves and an electric pump drive without using a hydraulic accumulator. In this context, planning of feasible trajectories is discussed for the investigated numerically and physically stiff multi-input multi-output system (MIMO). Additionally, a nonlinear two-degree-of-freedom control concept is designed by extension of the derived nonlinear feedforward controller with a PID feedback loop. The presented control schemes for trajectory tracking are examined in simulation and validated on testbed using real hydraulic hardware.